2017
DOI: 10.1002/ccd.27254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of IN.PACT DEEP trial on the association between changes in perfusion from pre‐ to postrevascularization and clinical outcomes in critical limb ischemia

Abstract: Improvements in toe pressure post revascularization are incremental and rarely normalize. Toe pressure, compared to ankle pressure, is more useful in CLI and predicts future MALE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Due to the nature of investigating a novel technique, there is limited established evidence to guide expected results for a sample size calculation. The most closely related published data are found in a subgroup analysis of the IN.PACT DEEP trial, which followed patients for 12 months after infrainguinal angioplasty 7. In patients who experienced any improvement of TBI immediately postoperatively, this study identified an HR of 0.15 (95% CI 0.04 to 0.57) of ‘MALE’ within 1 year, defined as major limb amputation above the level of the ankle, or major target lesion revascularisation in the form of thrombolysis, thrombectomy or bypass.…”
Section: Methods and Analysismentioning
confidence: 88%
See 2 more Smart Citations
“…Due to the nature of investigating a novel technique, there is limited established evidence to guide expected results for a sample size calculation. The most closely related published data are found in a subgroup analysis of the IN.PACT DEEP trial, which followed patients for 12 months after infrainguinal angioplasty 7. In patients who experienced any improvement of TBI immediately postoperatively, this study identified an HR of 0.15 (95% CI 0.04 to 0.57) of ‘MALE’ within 1 year, defined as major limb amputation above the level of the ankle, or major target lesion revascularisation in the form of thrombolysis, thrombectomy or bypass.…”
Section: Methods and Analysismentioning
confidence: 88%
“…The primary outcome of this study will be defined as MALE. The expected 1-year event rate of MALE is higher in subjects with critical limb ischaemia (20.5%7 vs subjects with claudication 3.2%) 20. Based on a recent 10-year audit of endovascular procedures performed at the investigational centre (The Ottawa Hospital, Civic Campus) the expected proportion of eligible subjects with critical limb ischaemia (vs claudication) is 0.625.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the current study by Hammad et al is small and underpowered, it should be seen as a call to arms for the societies who have a stake in vascular disease. It is time to come together on these important issues.…”
mentioning
confidence: 83%
“…In this issue of CCI , Hammad et al report a study in which they took a closer look at the IN.PACT Deep data and focused on methods of surveillance used in patients who underwent below knee endovascular revascularization for critical limb ischemia. In particular, they looked at the utility of ankle‐brachial index (ABI), ankle pressures, toe‐brachial index, and toe pressures in these groups.…”
mentioning
confidence: 99%